PENGGUNAAN INTERNET TERHADAP PENGETAHUAN REMAJA DALAM PENCEGAHAN KEHAMILAN YANG TIDAK DIINGINKAN - Ismiati, Ismiati (JURNAL MEDIA KESEHATAN, 2014)
Adolescent period is the phase of find out the identity and highly of curiosity. In Indonesia, information about reproductive health is still low, even though in the school. Most of the parents could not give satisfaction explanation about reproductive health to their children so most of them find out by the internet (social media). The purpose of this study was to analyze the factor of internet using, communication between parents and friends that influenced the knowledge and attitude of unwanted pregnancy prevention among adolescents in the public senior high school in Bengkulu. This study was used explanatory research method by approaching cross sectional.The result shows that a half of respondents (51.1%) have less information of reproductive internet using OR= 2.559.